Changes in Microbial Community Composition Related to Sex and Colon Cancer by Nrf2 Knockout - Song, Chin-Hee; Kim, Nayoung; Nam, Ryoung Hee; Choi, Soo In; Yu, Jeong Eun; Nho, Heewon; Surh, Young-Joon (Frontiers in Cellular and Infection Microbiology, 2021)
The frequency of azoxymethane/dextran sulfate sodium (AOM/DSS)-induced carcinogenesis in male mice is higher than that in female mice. Previous studies have reported that 17β-estradiol inhibits tumorigenesis in males by modulating nuclear factor-erythroid 2-related factor 2 (Nrf2). This study aimed to investigate the changes in mouse gut microbiome composition based on sex, AOM/DSS-induced colorectal cancer (CRC), and Nrf2 genotype. The gut microbiome composition was determined by 16S rRNA gene sequencing fecal samples obtained at week 16 post-AOM administration. In terms of sex differences, our results showed that the wild-type (WT) male control mice had higher alpha diversity (i.e. Chao1, Shannon, and Simpson) than the WT female control mice. The linear discriminant analysis effect size (LEfSe) results revealed that the abundances of Akkermansia muciniphila and Lactobacillus murinus were higher in WT male control mice than in WT female controls. In terms of colon tumorigenesis, the alpha diversity of the male CRC group was lower than that of the male controls in both WT and Nrf2 KO, but did not show such changes in females. Furthermore, the abundance of A. muciniphila was higher in male CRC groups than in male controls in both WT and Nrf2 KO. The abundance of Bacteroides vulgatus was higher in WT CRC groups than in WT controls in both males and females. However, the abundance of L. murinus was lower in WT female CRC and Nrf2 KO male CRC groups than in its controls. The abundance of A. muciniphila was not altered by Nrf2 KO. In contrast, the abundances of L. murinus and B. vulgatus were changed differently by Nrf2 KO depending on sex and CRC. Interestingly, L. murinus showed negative correlation with tumor numbers in the whole colon. In addition, B. vulgatus showed positive correlation with inflammatory markers (i.e. myeloperoxidase and IL-1β levels), tumor numbers, and high-grade adenoma, especially, developed mucosal and submucosal invasive adenocarcinoma at the distal part of the colon. In conclusion, Nrf2 differentially alters the gut microbiota composition depending on sex and CRC induction.